2019
DOI: 10.1002/solr.201900480
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Hydrogen Molybdenum Bronze in Solution‐Processed Interconnecting Layer for Efficient Nonfullerene Tandem Organic Solar Cells

Abstract: Tandem solar cells are attractive because they can break the Shockley–Queisser efficiency limit of single‐junction cells. However, it is still quite challenging to fabricate efficient nonfullerene tandem organic solar cells (OSCs) because of their complicated and vulnerable multilayers and interfaces. The interconnecting layer (ICL) between two subcells is the key part in efficient tandem solar cells, which should be designed properly based on the property of active layers. Herein, the incorporation of hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
(66 reference statements)
0
18
0
Order By: Relevance
“…Constructing a tandem structure is one of the most obvious ways of advancing the efficiency of solar cells by mitigating losses that come from photon transmission and thermalization. [ 114–122 ] Typically, tandem solar cells are made by stacking the multiple absorbers with complementary absorption spectra and by introducing so‐called a recombination layer that comprises of the combined bilayer of p‐type and n‐type electronic materials between the subcells. Recently, the highest efficiency of 17.3% has been reported in tandem OSCs using PBDB‐T:F‐M and PTB7‐Th:O6T‐4F:PC 71 BM as front subcell and back subcell photoactive layers, respectively, and it is theoretically predicted that efficiency of over 18% can be achieved through a combination of existing materials.…”
Section: Recent Progress In Device Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Constructing a tandem structure is one of the most obvious ways of advancing the efficiency of solar cells by mitigating losses that come from photon transmission and thermalization. [ 114–122 ] Typically, tandem solar cells are made by stacking the multiple absorbers with complementary absorption spectra and by introducing so‐called a recombination layer that comprises of the combined bilayer of p‐type and n‐type electronic materials between the subcells. Recently, the highest efficiency of 17.3% has been reported in tandem OSCs using PBDB‐T:F‐M and PTB7‐Th:O6T‐4F:PC 71 BM as front subcell and back subcell photoactive layers, respectively, and it is theoretically predicted that efficiency of over 18% can be achieved through a combination of existing materials.…”
Section: Recent Progress In Device Performancementioning
confidence: 99%
“…Initially, integrated solar cell research has been devoted to extending the light absorption bandwidth via incorporation of narrow bandgap polymer:fullerene acceptor‐based photoactive layer. [ 121–123,128,129 ] However, EQE of perovskite/BHJ integrated solar cells is still limited due to the relatively small amount of donor loading in BHJ and therefore resultant low gain in the near‐infrared region, as reflected in the EQE of the OSC itself. Recently, several researchers have turned to their attention to the NFA‐based OSCs to address this issue.…”
Section: Recent Progress In Device Performancementioning
confidence: 99%
“…[ 30 ] Similarly, the introduction of efficient transporting and recombination materials in OTSCs could be a competent approach toward minimizing V OC loss. [ 31–33 ] Moreover, a proper design of energy levels of organics will encourage V OC as well. In this case, the difference between the highest occupied molecular orbitals (HOMO) of the donating materials and lowest unoccupied molecular orbital (LUMO) of the acceptor is proportional to V OC .…”
Section: Fundamentals Of Loss Mechanisms In Single‐junction Solar Celmentioning
confidence: 99%
“…Apart from earlier discussions, there have two more important series: the benzo[1,2‐c:4,5‐c′]dithiophene‐4,8‐dione (BDD)‐based wide bandgap polymers, such as poly[(2,6‐(4,8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)‐benzo[1,2‐b:4,5‐b′]dithiophene))‐alt‐(5,5‐(1′,3′‐di‐2‐thienyl‐5′,7′‐bis(2‐ethylhexyl)benzo[1′,2′c:4′,5′‐c′]dithiophene‐4,8‐dione))] (PBDB‐T), [ 21,95–99 ] poly[(2,6‐(4,8‐bis(4‐fluro‐5‐(2‐ethylhexyl)thiophen‐2‐yl)‐benzo[1,2‐b:4,5‐b′] dithiophene))‐alt‐(5,5‐(1′,3′‐di‐2‐thienyl‐5′,7′‐bis(2‐ethylhexyl)benzo[1′,2′c:4′,5′‐c′]dithiophene‐4,8‐dione))] (PM6), [ 98,100 ] poly[dithieno[2,3‐d:2′,3′‐d′]benzo[1,2‐b:4,5‐b′]dithiophene‐co‐1,3‐bis(thiophen‐2‐yl)‐5′,7′‐bis(2‐ethylhexyl)benzo‐[1,2‐c:4,5‐c′]dithiophene‐4,8‐dione] (PDBT‐T1), [ 101 ] poly[5′,7′‐bis(2‐ethylhexyl)benzo‐[1,2‐c:4,5‐c′]dithiophene‐4,8‐dione‐alt‐3″,4′‐difluoro‐2,2′:5′,2″:5″,2‴‐quaterthiophene‐5,5‴‐diyl] (PBDD4T‐2F), [ 80 ] poly[(2,6‐(4,8‐bis(3‐(hexyloxy)thiophen‐2‐yl)‐benzo[1,2‐b:4,5‐b′]dithiophene))‐alt‐(5,5‐(1′,3′‐di‐2‐thienyl‐5′,7′‐bis(2‐ethylhexyl)benzo[1′,2′c:4′,5′‐c′]dithiophene‐4,8‐dione))] (PBD1) [ 102 ] and so on, and the thieno[3,4‐b]thiophene (TT)‐based low‐bandgap polymers, such as poly[4,8‐bis(2‐ethylhexyloxy)benzo[1,2‐b:4,5‐b′]dithiophene‐co‐3‐fluorothieno[3,4‐b]thiophene‐2‐carboxylate] (PTB7), [ 86 ] poly[4,8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1,2‐b:4,5‐b′]dithiophene‐co‐3‐fluorothieno[3,4‐b]thiophene‐2‐carboxylate] (PTB7‐Th), [ 98,102,103 ] poly[4,8‐bis(5(2‐ethylhexyl)‐thiophene‐2‐yl)‐benzo[1,2‐b54,5‐b9]dithiophenealt alkylcarbonylthieno[3,4‐b]thiophene] (PBDTTT‐C‐T), [ 60,104,105 ] poly[4,8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1,2‐b:4,5‐b′]dithiophene‐co‐thieno[3,4‐b]thiophene‐2‐carboxylate] (PBDTTT‐E‐T), [ 80,95 ] and so on. Using the BDD‐based wide bandgap polymers in the bottom cell and TT‐based polymers in the top cell as well as pairing with desirable fullerenes and NFAs have been demonstrated to be a successful choice to construct high‐performance tandem OSCs.…”
Section: Photoactive Materials For Tandem Oscsmentioning
confidence: 99%
“…[ 21,33,38–40,58,70,75–77,85,97,99,102,122,127–129,132,138,144,164,208 ] Zhou and coworkers found that PEDOT:PSS with surfactant deposited on top of nonfullerene‐based tandem OSCs might lead to chemical reaction between PEDOT:PSS and the NFA (IT‐4F), which would be detrimental to the device performance. [ 100 ] To avoid the direct deposition of PEDOT:PSS on top of the active layer, they introduced a hydrogen molybdenum bronze (H x MoO 3 ) layer between the bottom active layer and PEDOT:PSS. The introduction of H x MoO 3 could well form a uniform film on the active layer surface and provide a hydrophilic surface for the following uniform deposition of PEDOT:PSS film.…”
Section: The Icls For Tandem Oscsmentioning
confidence: 99%